Alimentação de juvenis de carpa capim (Ctenopharyngodon idella) com diferentes níveis de fibra na dieta - Cardoso, Matheus dos Santos (2015)
The objective of the study was to evaluate the growth performance of grass carp fed with different levels crude fiber in the diet, using as a main fibrous ingredient rice hull. We used 180 juveniles grass carp with standard length of 7.09 ± 0.43cm, weighing 6.78 ± 1.11g, randomly distributed in 15 units of 40 L, with 12 fish per unit. The daily feed management was the offer of 3% of body weight of feed and 3% of body weight of forage gender Cynodon spp. during 36 days. The diets were formulated with five levels of rice hull (0%; 3%; 6%; 9% and 12%) getting increasing levels of crude fiber (3.18%; 4.64%; 6.15%; 7.09% and 7.79%) in completely randomized design with five treatments and three replications. The physical and chemical parameters of water remained within the levels for the cultivation of the species. Among the variables analyzed, weight gain, specific growth rate, condition factor and the forage consumption were not statistically different (P> 0.05) between the diets. The weight gain and feed conversion had a negative correlation (P <0.05) with the increase of rice hull levels. It was concluded that the inclusion of up to 9% of rice hull in grass carp juveniles diet can be used without affecting the performance of the animals.